2011
DOI: 10.1001/jama.2011.766
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Screening on Ovarian Cancer Mortality

Abstract: Among women in the general US population, simultaneous screening with CA-125 and transvaginal ultrasound compared with usual care did not reduce ovarian cancer mortality. Diagnostic evaluation following a false-positive screening test result was associated with complications. Trial Registration clinicaltrials.gov Identifier: NCT00002540.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
412
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,114 publications
(421 citation statements)
references
References 23 publications
3
412
0
6
Order By: Relevance
“…The median number of NAC cycles in the whole population was 6 (range 4-7) - 4 (range 3-4) in group 1 and 6 (range 6-7) in group 2. The median number of cycles of adjuvant chemotherapy after IDS for the whole study population was 3 [2,3,4]. There was no statistically significant difference between both groups (p = 0.14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median number of NAC cycles in the whole population was 6 (range 4-7) - 4 (range 3-4) in group 1 and 6 (range 6-7) in group 2. The median number of cycles of adjuvant chemotherapy after IDS for the whole study population was 3 [2,3,4]. There was no statistically significant difference between both groups (p = 0.14).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 75% of new diagnoses are made at FIGO stage III or IV [2], with an overall 5-year survival rate of about 37% [3]. Neither screening methods nor prevention have been shown to be effective [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…It is especially important to survey women with HBOC after a breast cancer diagnosis because many of them will survive their breast cancer but remain at risk for ovarian cancer, which has a higher mortality rate. Furthermore, current screening protocols for ovarian cancer, including transvaginal ultrasound and monitoring of serum CA-125 concentration, lack sensitivity and specificity and do not reduce the overall risk for mortality [34]. Bilateral salpingo-oophorectomy has been well established as a successful method for the prevention of ovarian and fallopian tube cancers in BRCA1 and BRCA2 carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The performance characteristics of screening strategies in ovarian cancer along with their cost effectiveness have been evaluated in two large screening studies [10][11]. The PLCO study reported that simultaneous screening with CA125 and transvaginal ultrasound did not reduce ovarian cancer mortality and in fact, the diagnostic evaluation following the false positive result was associated with complications [10].…”
Section: Introductionmentioning
confidence: 99%
“…The PLCO study reported that simultaneous screening with CA125 and transvaginal ultrasound did not reduce ovarian cancer mortality and in fact, the diagnostic evaluation following the false positive result was associated with complications [10]. It is yet to be determined whether the UKCTOCS trial has demonstrated a reduction in mortality or a stage shift, as data from long-term follow-up are awaited [11].…”
Section: Introductionmentioning
confidence: 99%